STORYTELLING INTERAKTIF DENGAN KAMISHIBAI SEBAGAI SARANA PENGUATAN BONDING ORANG TUA DAN ANAK USIA DINI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The bond between parents and children is the main foundation in early childhood development. A warm, secure, and comfortable emotional bond will help build children’s psychological well-being. One way to build a strong bond between parents and children is through simple activities such as storytelling using kamishibai. This study aims to describe the process and experiences of parents participating in interactive storytelling workshops using kamishibai as a means of strengthening the bond between parents and children. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the use of kamishibai media greatly contributes to parents’ storytelling abilities and strengthens the emotional bond between parents and children. The use of kamishibai media creates warmer, more responsive, and communicative interactions, as well as creating moments of greater closeness between parents and children.